2018
DOI: 10.3892/mmr.2018.9399
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxysafflor yellow A protects against angiotensin II‑induced hypertrophy

Abstract: Myocardial infarction (MI) is life-threatening and is generally accompanied by myocardial hypertrophy. Notably, Hydroxysafflor yellow A (HSYA) can prevent tissue injuries. The objective of this study was to investigate the effect of HSYA on hypertrophy after MI. Hematoxylin and eosin (H&E) staining assays were performed to measure cell area. The protein synthesis rate was assessed using the 3H Leucine incorporation assay. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR), western blot anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In this study, ANGII was chosen to establish the PCH model, ANP and BNP mRNA levels increased significantly after 0.5 μM ANGII stimulation for 24 h. This may be caused by the inhibition of transcription and expression of natriuretic peptide receptor A (ANP and BNP receptors) [ 20 ]. In addition to ANP and BNP, the low-expression of the α-myosin heavy chain (α-MHC) and over-expression of the β-myosin heavy chain (β-MHC) gene expression were also observed in the PCH model [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, ANGII was chosen to establish the PCH model, ANP and BNP mRNA levels increased significantly after 0.5 μM ANGII stimulation for 24 h. This may be caused by the inhibition of transcription and expression of natriuretic peptide receptor A (ANP and BNP receptors) [ 20 ]. In addition to ANP and BNP, the low-expression of the α-myosin heavy chain (α-MHC) and over-expression of the β-myosin heavy chain (β-MHC) gene expression were also observed in the PCH model [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperactivity of MAPKs (JNK, P38, ERK) signal pathways can also be observed in PCH models and could result in transforming PCH to malignant heart failure [ 36 ]. Natural alkaloids berberine was proven to inhibit PCH through the AMPK pathway [ 21 ]. The CaN-NFAT signal pathway is regulated by Ca 2+ and is directly related to the expression of fetal genes.…”
Section: Discussionmentioning
confidence: 99%
“…Carthamus tinctorius L. has been used for thousands of years, and its traditional applications include promoting blood circulation, clearing blood stasis, and relieving pain [31,32]. HSYA, one of the main active ingredients of Carthamus tinctorius L., has a flavonoid structure and excellent antioxidant activity [16,33].…”
Section: Discussionmentioning
confidence: 99%
“…A specialized piece of in vivo research demonstrated that the antioxidant effect of HSYA was involved in the prevention of Ang II-induced myocardial hypertrophy (a compensatory response to MI), which may act through the activation of the nuclear factor erythroid-2-related factor 2 (Nrf2)/NAD(P)H: quinone oxidoreductase 1/HO-1 signaling pathway (Ni et al, 2018). Nrf-2, as the main regulator of the antioxidant system present on the cardiovascular system, is becoming a very promising pharmacological target for cardiovascular diseases (McSweeney et al, 2016).…”
Section: Therapeutic Potential Of Hsya On Ccvds Effects On Myocardialmentioning
confidence: 99%
“…Promotes endothelial progenitor cells function through the HO-1/VEGF-A/stromal cell-derived factor-1a signaling cascade (Wei et al, 2017) MI model in male SD rats 2, 5 mg•kg -1 i.p. Activates the Nrf2/NAD(P)H:quinone oxidoreductase 1/HO-1 signaling pathway (Ni et al, 2018) Ang II-induced H9c2 cells 80 mmol•L -1 / Increases the cell viability, however, reduces protein synthesis rate, mitigates cell surface area and decreases the expression of brain natriuretic factor and b-myosin heavy chain (Ni et al, 2018) Myocardial ischemia/ reperfusion (MI/ R) injury MI/R model in male SD rats 5 mg•kg -1 i.p. Decreases JAK2/signal transducer and activator of transcription 1 activity, enhances antioxidant capacity and decreases apoptosis (Zhou et al, 2019) Hyperlipidemia combined with MI/R model in male Wistar rats 8, 16, 32 mg•kg -1 i.p.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%